Assessing digital transformation within a South African mining firm - Benzane, Mahene Patrice (My University, 2019)
South Africa is still one of the top global producers of various mineral commodities, including gold, coal, platinum, palladium, manganese, titanium, and uranium. The mining industry contributes about 8% to the GDP of South Africa, and it used to be a dominant sector in the past. This industry is known to be a labour-intensive sector with little application of the digital technologies which many industries that were born after the boom of mining in South Africa are currently using. The recent example is the increasing depth of gold which tends to require technology interventions to access these resources where it is not feasible for physical humankind intervention, and this shows the need to transform the mines digitally. The effects of various digital technologies in the mining industry due to the Fourth Industrial Revolution (4IR) phenomenon means that mining organisations can mine smarter, improve safety, reduce cost, develop new insights from their current operation, and contribute towards the sustainable economic and social development of the country. However, the required level of digital maturity, the applicable digital transformation model in terms of what to digitally transform within the mining value chain, as well as understanding the mechanism required to drive maximum adoption and successful implementation of these digital technologies across all levels of the organisation remains unclear and challenging. In a quest to address these, a qualitative research strategy was selected as a means of getting to understand what needs to be digitally transformed in the mining value chain, this would then help identify an applicable Digital Transformation Framework for a mining firm willing to embark on this transformation journey. This qualitative approach is further used in the research to unpack the effective ways to engage various stakeholders within the organisation to help enable successful implementation and adoption of these digital technology initiatives. To do this, a single case study method was utilised and Company X was identified as an ideal mining company in which to conduct the study. Company X has embarked on a digital transformation journey which they run through an internal initiative called Digital@Comapany X, and they have been making a buzz across the South African mining industry as the pioneers in adopting and embracing digitisation in mining, hence they were selected for this study. Based on the reviewed literature, the research made several propositions. One of the propositions indicated that the digital transformation of the internal processes within the mining value chain is the key area of focus for a South African mining firm. The key findings from this case showed that 100% of the interviewed executives, junior managers, middle managers, and senior managers believe that the introduction of the digital technologies within Company X will lead to worker enablement through digitised processes that will eventually improve decision making by using the power of visualised data. Therefore, according to the first proposition made, it is evident from the research that digitalisation of the internal process within the mining value chain is an important area of focus. In summary, the findings showed the following areas as what the digital transformation initiative aims to transform: Digital Capability, Human Resources, Worker Enablement, Culture, Customer Experience, Process Digitisation, Unified Data, and Performance Management. 50% of the executives indicated the importance of customer experience in their digital transformation journey. 65 % of the respondents indicated the importance of unified data by having integrated operations centres, whereas 36% mentioned performance management as the key area of focus, and only 14% of the respondents mentioned IT infrastructure to enhance digital capability as another focus area for the internal digital transformation journey. According to the reviewed literature, it was further proposed that the Digital Piano framework is the most appropriate or relevant transformation model to be used by Company X, and can be further tested by mining firms intending to embark on a digital transformation journey. The aim was to test this proposition by comparing what to transform in practice according to Digital@Company X roadmap to what other various theoretical and conceptual frameworks focus on in terms of the digital transformation process. The findings were not entirely in agreement with the proposition made. Based on what is currently done at Company X, the combination of these following frameworks in the context of the mining firm proves to be more appropriate than using a specific model: Digital Piano framework, Digital Orchestra Framework, Six Keys to Success Framework, Digital Enterprise Integrative Management Framework, Digital Transformation Framework, by Corver and Elkhuizen, The Digital Reinvention Framework, and the Digital Innovation Strategy Framework. Therefore, choosing a single framework from the literature to apply to the mine as a relevant digital transformation strategy may have a dire digital transformation process or journey that leads to poor implementation, lack of adoption and wastage of resources with no realisation of intended digital benefits if it does not holistically cover various aspects of the mine or organisation as a whole. The researcher named the combination of these frameworks an Integrated Digital Transformation Framework for Mining (IDTFM). The last proposition made in this research was that to embark on the digital transformation journey in the mining sector in the 4IR era requires the co-operation and participation of all stakeholders to ensure the successful implementation and adoption of digital technology initiatives. According to the findings, the following themes in terms of what may or may not lead to success emerged: Poor Change Management, Unclear Vision, Value Realisation, Stakeholder Involvement, and Ease of Use and Adoption. According to the findings gathered from the 14 respondents, it is evident that there is a clear understanding of what could lead to the failure of digital technology interventions within Company X. Respondents further echoed the importance of change management, vision, stakeholder engagement, the value brought by these technologies as well as the importance of Ease of use to drive adoption. The managers have a strong interest in the practicality of any IT system implemented to drive productivity and efficiency, and the ease of use of the system is an important factor for them as key stakeholders that need to drive these initiatives at the operations. 80% of all the respondents emphasised on the ease of use. 57% indicated the importance of stakeholder involvement, and further findings showed the significance of good change management is one of the driving factors for successful implementation and adoption. In addition to these findings, one of the two executives interviewed highlighted the importance of everyone understanding the vision of the company. Therefore, the third proposition is validated through the research findings and literature that any lack of effective stakeholder engagement when pursuing a digital transformation roadmap or efforts within a mining firm will lead to a lack of adoption and ineffective implementation. To link some of the findings to the literature, the Diffusion of Innovations Theory developed by E.M. Rogers in 1962, states that Innovation, communication channels, time, and social system are the four key components of the diffusion of innovations, and when promoting innovation to a target population, it is important to understand the characteristics of the target population that will help or hinder the adoption of the innovation. The Technology Acceptance Model (TAM) theoretical framework helps explain the usage of technology within a specific context, and the usage could either be the ease of use or the usefulness of that specific technology as perceived by the users (Venkatesh and Bala, 2008). Therefore, based on the 80% of the respondents believing that the ease of use of these technologies and the perceived usefulness in terms of practical application will lead to easier adoption indicates that TAM is accurate in the case of Company X. Therefore, the research further recommends the use and applications of these theories when embarking on the digital transformation journey of a mine. Further to these findings, the Diffusion of Innovations Theory has been used successfully in many industries including communication, agriculture, public health, criminal justice, social work, and marketing, therefore it can also be applied in a case of a mining firm to ensure adoption of innovations brought in the form of digital technology implementations. TAM is also applicable in the context of a mining firm and must be utilised. With the support of literature and the findings of the research, It is further recommended that the leadership team in a mining firm must create and follow an integrated digital transformation compass (Westerman, Bonnet & McAfee, 2014).
A research report submitted in fulfilment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2020
Keywords: Mining industry; Mining; South Africa; Fourth Industrial Revolution (4IR); SDG-8: Decent work and economic growth